(untitled) (Journal of EAHIL, 2025)
In alignment with the University of Bern’s broader efforts to combat discrimination and uphold inclusivity, The Medical Library (BibMED) at the University of Bern has launched the Caring Library initiative. This initiative promotes a safe, welcoming space through twenty guiding principles displayed prominently behind the information desk. These principles, such as respect, inclusion, and solidarity, serve as a daily reminder of the values that keep our community caring and discrimination-free. This article describes the motivations behind the Caring Library initiative. The BibMED is committed to fostering an environment where all backgrounds and identities are valued and respected.